Publication Trend in the Journal of Psychiatrists’ Association of Nepal (Journal of Psychiatrists' Association of Nepal, 2026)
Background: Evaluating trends in journals are crucial as they offer valuable insights into research trends. We aim to evaluate the characteristics and trends of articles published in the Journal of Psychiatrists’ Association of Nepal (JPAN), an official journal of the Psychiatrists’ Association of Nepal (PAN).Methods: A bibliometric review was conducted by accessing all volumes of the online database of the JPAN. Articles were classified on the basis of psychiatry subspecialty, type of article, study design and study site. Data was entered and analyzed in Microsoft Excel. Descriptive statistics was used to calculate frequency and percentages.Result: A total of 275 articles from 14 volumes published between 2011 to 2025 were studied. Total number of articles per issue is steady over the years with a mean of 19.64 articles per year. Maximum number (n=27) of articles were published in the year 2019. Majority ofarticles were based on general mental health followed by liaison psychiatry, addiction psychiatry, adult psychiatry and child and adolescent psychiatry. One hundred and seventy one studies were cross sectional followed by 12 retrospective studies, 6 case control studies and 3 randomized controlled trials. Based on article type, original research articles (ORA) constituted the majority (71.3%, n = 196). Most studies (81.3%, n = 192) were conducted in hospital-based settings.Conclusion: Our findings indicate that research publications in JPAN demonstrate a gradual upward trend. There is a need to diversify research topics, enhance methodological rigor, and promote generation of higher level-evidence.